ANALISIS PENGARUH BAURAN PEMASARAN TERHADAP KEPUASAN PELANGGAN KARTU PASCABAYAR HALO DI KOTA AMUNTAI - ROHANA FARIDAH; NOOR RISMAWATI (Islamic Economics and Business Faculty of UIN Antasari, 2013)
The purpose of this research is to describe the influence of the marketing mix (X), whichconsists of four variables: product, price, promotion, and place, toward the customer satisfaction (Y).The result of the double linear regression shows that the marketing mix influences the satisfaction asmuch as 28,4%. Simultaneously, the marketing mix variables (product, price, promotion, and place)influence Halo postpaid card customer satisfaction in Amuntai. This phenomena is shown throughthe result value sig 0.000 which is smaller than the value ? 0,05. The result of the data analysis alsoshows that the promotion variable (X3) is the most dominant dimension/aspect which influences theHalo postpaid card customer satisfaction. This finding can be seen through the unstandardizedcoefficients value as much as 0,236 , standardized coefficients as much as 0,262, and also through the sig feeas much as 0,054.